Photocatalytically degraded polyethylene coated paper and preparation method thereof
By adding erucic amide, silicone powder, nano-inorganic filler and titanium dioxide-loaded Mxene material to the polyethylene coating paper, the photocatalytic degradation performance is improved, and the problem of difficult degradation of polyethylene coating paper is solved, achieving the effect of rapid degradation while maintaining physical properties.
Patent Information
- Application Number
- CN202510044231.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-11
AI Technical Summary
Polyethylene coating paper is difficult to decompose by microorganisms in the natural environment, resulting in environmental pollution. Existing improved methods such as adding biodegradable agents or using degradable polymers have problems such as degrading physical properties or increasing production costs.
Polyethylene coating paper with photocatalytic degradation is used to improve its physical and mechanical properties and photocatalytic degradation properties by adding erucic amide, silicone powder, nano-inorganic fillers and titanium dioxide-supported Mxene material to the polyethylene as photooxygen degradation masterbatches.
While maintaining good physical properties, polyethylene coating paper can quickly degrade under light conditions, improve degradation efficiency and reduce environmental pollution.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coated paper processing technology, and more specifically, to a photocatalytically degradable polyethylene coated paper. Background Art
[0002] Laminated paper is a composite material made by coating plastic particles on the surface of paper through a casting machine. Polyethylene laminated paper is a commonly used packaging material. It is widely used in packaging in the food, medicine, agriculture and other industries due to its excellent physical properties and chemical stability. However, while polyethylene laminated paper brings convenience, it also brings serious environmental pollution problems. Since the chemical structure of polyethylene is stable and difficult to be decomposed by microorganisms in the natural environment, traditional polyethylene laminated paper often exists in the environment for a long time after being discarded, causing environmental problems such as soil pollution and water pollution.
[0003] In order to solve the degradation problem of polyethylene coated paper, researchers have conducted a lot of research. At present, there are some methods to try to improve the degradability of polyethylene coated paper, such as adding biodegradable agents, using degradable polymers to replace polyethylene, etc. However, these methods still have certain limitations in practical applications. For example, adding biodegradable agents may reduce the physical properties of polyethylene coated paper and affect its use effect; while using degradable polymers to replace polyethylene may increase production costs and limit its wide application.
[0004] Therefore, it is particularly important to develop a new material that not only maintains the excellent physical properties of polyethylene coated paper but also can be rapidly degraded in the natural environment. Summary of the invention
[0005] In order to achieve the degradation of polyethylene coated paper while maintaining the good physical properties of polyethylene, the present application provides a photocatalytically degradable polyethylene coated paper and a preparation method thereof.
[0006] In the first aspect, the present application provides a photocatalytically degradable polyethylene coated paper, which adopts the following technical solution: A photocatalytically degradable polyethylene coated paper comprises the following raw materials in parts by weight: 70-80 parts of polyethylene, 0.5-0.8 parts of erucic acid amide, 1-3 parts of photo-oxidation degradation masterbatch, 0.2-2 parts of silicone powder, 0.1-0.5 parts of photosensitizer, and 1-3 parts of nano inorganic filler. The photo-oxidation degradation masterbatch is obtained by loading titanium dioxide on Mxene material.
[0007] By adopting the above technical solution, the addition of erucamide significantly improves the physical and mechanical properties of the coated paper. By reducing the friction and adhesion between the polyethylene molecular chains, the smoothness and slipperiness of the coated paper are effectively improved, which not only makes the coated paper smoother during use, but also improves its overall flexibility. Further erucamide also enhances the tensile strength and elongation at break of the coated paper, significantly enhancing the more excellent mechanical properties of the coated paper when facing external forces. With its good compatibility and miscibility, silicone powder can form a uniform mixture with polyethylene molecular chains, thereby reducing the melt viscosity of polyethylene during processing, making it easier to flow, effectively preventing defects such as bubbles and small particles on the polyethylene surface, and improving the mechanical properties of the coated paper.
[0008] Nano inorganic fillers have a large specific surface area and high surface activity, and can form a strong interaction force with polyethylene molecular chains, thereby improving the strength of the coated paper. When the coated paper is subjected to a large external force, it can maintain the stability and integrity of its structure.
[0009] The addition of photocatalytic degradation masterbatch gives the coated paper excellent photocatalytic degradation performance. Titanium dioxide is a commonly used photocatalyst that can catalyze the degradation reaction of polyethylene under light conditions, thereby achieving rapid degradation of the coated paper. By attaching titanium dioxide to the Mxene material, not only the degradation rate is increased, but also the compatibility and dispersion uniformity with other raw materials are enhanced, while the overall mechanical properties of the coated paper are improved, so that the coated paper has environmental protection characteristics while maintaining good performance.
[0010] Optionally, the photo-oxidative degradation masterbatch preparation comprises the following steps: (1) dissolving tetrabutyl titanate in a mixed solution of ethanol and deionized water, adding aryl triazole and sodium dodecyl sulfate, and dropping potassium permanganate solution at 150-200° C. while stirring and reacting for 8-10 hours; (2) The temperature is lowered to 35-40° C., and the Mxene material is added and sealed and ultrasonicated until it is evenly dispersed. After reacting for 2-3 hours, the material is washed and dried to obtain a photo-oxidative degradation masterbatch.
[0011] By adopting the above technical solution, the aromatic triazole molecules have the ability to absorb radiation energy and produce electronic transitions. This property can enhance the material's absorption and utilization efficiency of light. By combining the aromatic triazole molecules with silicon dioxide, the photosensitivity of titanium dioxide can be further improved, making the photocatalytic degradation process more efficient.
[0012] The prepared photo-oxidative degradation masterbatch is added to polyethylene to stimulate the silicon dioxide attached thereto to photocatalytically degrade polyethylene by absorbing light. At the same time, MXene is unstable under environmental conditions and is easily degraded by oxidation, which further accelerates the degradation efficiency of polyethylene. In addition, the MXene material presents a multi-layer sheet shape, and the attachment of titanium dioxide on it can improve the compatibility between titanium dioxide and the raw materials, making them easier to mix, so that the raw materials of the polyethylene coated paper are evenly dispersed, thereby improving the photocatalytic performance of the catalyst.
[0013] Optionally, the photo-oxidative degradation masterbatch includes 4-6 parts of tetrabutyl titanate, 1-2 parts of sodium dodecyl sulfate, 16-20 parts of ethanol, 2-4 parts of water, 1-3 parts of potassium permanganate solution, 0.03-0.05 parts of aromatic triazole, and 8-10 parts of Mxene material.
[0014] Optionally, the nano inorganic filler is any one of nano montmorillonite, talc and mica.
[0015] Optionally, the nano inorganic filler is obtained by surface activation modification, which specifically includes the following steps: After the nano inorganic filler is dispersed in water, a proper amount of titanate coupling agent is added and ultrasonic stirring is performed, and the mixture is reacted at room temperature for 1-2 hours. After the reaction is completed, the modified nano inorganic filler is obtained by drying.
[0016] By adopting the above technical solution, nano inorganic fillers can be evenly dispersed in the polyethylene matrix, reducing the melt viscosity of the material, which not only improves the fluidity of the melt and improves the processing performance, but also the unique size effect of nano materials can further enhance the tensile strength and elongation at break of the coated paper.
[0017] Optionally, the photosensitizer is dibutyl iron dithiocarbamate.
[0018] By adopting the above technical solution, when used in combination with the photo-oxidative degradation masterbatch, ferric dibutyl dithiocarbamate can further enhance the effect of photocatalytic degradation. Titanium dioxide, as a photocatalyst, can produce active species such as hydroxyl radicals under light, which act together with the free radicals produced by ferric dibutyl dithiocarbamate on the polyethylene molecular chain to accelerate its degradation process.
[0019] Optionally, 0.3-0.5 parts of phthalocyanine ketone are also added to the raw materials.
[0020] By adopting the above technical solution, phthalocyanine ketone can absorb light energy and convert it into chemical energy, thereby initiating or accelerating the photocatalytic degradation process of polyethylene molecules. The improvement of its photosensitivity helps to enhance the photodegradation efficiency of coated paper, allowing polyethylene to be decomposed into small molecules faster under light conditions, thereby achieving the purpose of improving degradation efficiency.
[0021] In a second aspect, the present application provides a method for preparing photocatalytically degradable polyethylene coated paper, using the following technical solution: A method for preparing photocatalytically degradable polyethylene coated paper comprises the following steps: (1) Evenly mix polyethylene, photo-oxidative degradation masterbatch, silicone powder and erucamide; (2) heating and melting the mixture, adding photosensitizer and nano inorganic filler, and continuing to disperse and mix; (3) Spraying the obtained coating material onto the base paper, and obtaining the photocatalytically degradable polyethylene coating paper after drying.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application introduces the photo-oxidative degradation masterbatch obtained by loading titanium dioxide with Mxene material, the photocatalytic degradation performance of the coated paper is significantly improved while the dispersion uniformity of titanium dioxide in the polyethylene base material is improved, so that the coated paper can be decomposed into small molecules faster while maintaining good mechanical properties, thereby improving the degradation efficiency.
[0023] 2. In this application, Mxene material is preferably used as a catalyst for silica. On the one hand, it is easily oxidized in air and humid environments, accelerating the degradation process. On the other hand, it has good mechanical properties itself, and its addition further improves the tensile strength and breaking strength of the coated paper.
[0024] 3. The surface activated and modified nano inorganic fillers in this application can be evenly dispersed in the polyethylene matrix, reducing the melt viscosity of the material and improving the fluidity of the melt, thereby obtaining better processing performance. At the same time, the Mxene material presents a multi-layered sheet form, making it easier for titanium dioxide to adhere to it, improving the compatibility between titanium dioxide and the raw materials and making them easier to mix. Under the combined effect of these measures, the raw materials of the coated paper are evenly dispersed, the photocatalytic performance of the catalyst is improved, and the overall performance of the coated paper is further improved. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0027] 1,2,3-Benzotriazole was purchased from Shandong Longhui Chemical Co., Ltd., CAS No. 95-14-7; single-layer Nb4C3Tx MXene powder was purchased from Xinxin Technology Co., Ltd.; polyethylene was purchased from Shouguang Hongchuang Environmental Protection Technology Co., Ltd., model CPE135C; Preparation examples of raw materials and / or intermediates Preparation Example 1 A photo-oxidative degradation masterbatch, the preparation of which comprises the following steps: (1) 4 kg of tetrabutyl titanate was dissolved in a mixed solution of 18 kg of ethanol and 4 kg of deionized water, 0.04 kg of 1,2,3-benzotriazole and 1 kg of sodium dodecyl sulfate were added, and 1 kg of potassium permanganate solution with a mass concentration of 0.02% was added dropwise while stirring, and the mixture was reacted at 180° C. for 9 hours; (2) The reaction temperature was lowered to 40°C, 9 kg of Mxene material was added and sealed and ultrasonicated until uniformly dispersed. After reacting for 2 hours, the mixture was repeatedly washed with ethanol and deionized water, and then dried in a vacuum drying oven at 60°C to obtain a photo-oxidative degradation masterbatch.
[0028] Preparation Example 2 A photo-oxidative degradation masterbatch, the preparation of which comprises the following steps: (1) 5 kg of tetrabutyl titanate was dissolved in a mixed solution of 16 kg of ethanol and 3 kg of deionized water, 0.03 kg of 1,2,3-benzotriazole and 2 kg of sodium dodecyl sulfate were added, and 2 kg of potassium permanganate solution with a mass concentration of 0.02% was added dropwise while stirring, and the mixture was reacted at 150° C. for 8 hours; (2) The reaction temperature was lowered to 35°C, 8 kg of Mxene material was added and sealed and ultrasonicated until uniformly dispersed. After reacting for 2 hours, the mixture was repeatedly washed with ethanol and deionized water, and then dried in a vacuum drying oven at 60°C to obtain a photo-oxidative degradation masterbatch.
[0029] Preparation Example 3 A photo-oxidative degradation masterbatch, the preparation of which comprises the following steps: (1) 6 kg of tetrabutyl titanate was dissolved in a mixed solution of 20 kg of ethanol and 2 kg of deionized water, 0.05 kg of 1,2,3-benzotriazole and 1.5 kg of sodium dodecyl sulfate were added, and 3 kg of potassium permanganate solution with a mass concentration of 0.02% was added dropwise while stirring, and the mixture was reacted at 180° C. for 9 hours; (2) The reaction temperature was lowered to 38°C, 10 kg of Mxene material was added and sealed and ultrasonicated until uniformly dispersed. After reacting for 2 hours, the mixture was repeatedly washed with ethanol and deionized water, and then dried in a vacuum drying oven at 60°C to obtain a photo-oxidative degradation masterbatch.
[0030] Preparation Example 4 A photo-oxidative degradation masterbatch, which is different from Preparation Example 1 in that no Mxene material is added in this Preparation Example, specifically comprises the following steps: (1) 4 kg of tetrabutyl titanate was dissolved in a mixed solution of 18 kg of ethanol and 4 kg of deionized water, 0.04 kg of 1,2,3-benzotriazole and 1 kg of sodium dodecyl sulfate were added, and 1 kg of potassium permanganate solution with a mass concentration of 0.02% was added dropwise while stirring, and the mixture was reacted at 180° C. for 9 hours; (2) The reaction temperature was lowered to 40°C, and the mixture was sealed and ultrasonically dispersed uniformly. After standing for 2 hours, the mixture was repeatedly washed with ethanol and deionized water, and then dried in a vacuum drying oven at 60°C to obtain a photo-oxidative degradation masterbatch.
[0031] Preparation Example 5 A photo-oxidative degradation masterbatch, which is different from Preparation Example 1 in that no aryl triazole is used to pre-sensitize silica in this Preparation Example, specifically comprising the following steps: (1) 4 kg of tetrabutyl titanate was dissolved in a mixed solution of 18 kg of ethanol and 4 kg of deionized water, 1 kg of sodium dodecyl sulfate was added, and 1 kg of potassium permanganate solution with a mass concentration of 0.02% was added dropwise while stirring, and the mixture was reacted at 180° C. for 9 hours; (2) The reaction temperature was lowered to 40°C, 9 kg of Mxene material was added and sealed and ultrasonicated until uniformly dispersed. After reacting for 2 hours, the mixture was repeatedly washed with ethanol and deionized water, and then dried in a vacuum drying oven at 60°C to obtain a photo-oxidative degradation masterbatch.
[0032] Preparation Example 6 A modified nano inorganic filler, the preparation of which comprises the following steps: 3 kg of nano-montmorillonite was dispersed in 5 kg of water, and then 1.5 kg of isopropyl tri(isostearoyl) titanate was added and ultrasonically stirred. The mixture was reacted at room temperature for 2 h. After the reaction was completed, the modified nano-inorganic filler was obtained by drying. Example
[0033] Example 1 A photocatalytically degradable polyethylene coated paper, the preparation of which comprises the following steps: (1) 75 kg of polyethylene, 2 kg of the photo-oxidative degradation masterbatch prepared in Preparation Example 1, 1.1 kg of silicone powder, and 0.65 kg of erucamide were uniformly mixed; (2) heating the mixture to 180° C. to melt the mixture, adding 0.25 kg of dibutyl iron dithiocarbamate (photosensitizer) and 3 kg of nano-montmorillonite (nano-inorganic filler), and continuing to disperse and mix; (3) Add the obtained coating material into the hopper of the coating machine, and at the same time load the base paper into the coating machine, spray the coating material onto the base paper, and obtain the photocatalytically degradable polyethylene coated paper after cooling and drying.
[0034] Example 2 A photocatalytically degradable polyethylene coated paper, the preparation of which comprises the following steps: (1) 70 kg of polyethylene, 3 kg of the photo-oxidative degradation masterbatch prepared in Preparation Example 1, 0.2 kg of silicone powder, and 0.8 kg of erucamide were uniformly mixed; (2) heating the mixture to 180° C. to melt the mixture, adding 0.1 kg of dibutyl iron dithiocarbamate (photosensitizer) and 1 kg of nano talc (nano inorganic filler), and continuing to disperse and mix; (3) Add the obtained coating material into the hopper of the coating machine, and at the same time load the base paper into the coating machine, spray the coating material onto the base paper, and obtain the photocatalytically degradable polyethylene coated paper after cooling and drying.
[0035] Example 3 A photocatalytically degradable polyethylene coated paper, the preparation of which comprises the following steps: (1) 80 kg of polyethylene, 1 kg of the photo-oxidative degradation masterbatch prepared in Preparation Example 1, 2 kg of silicone powder, and 0.5 kg of erucamide were mixed uniformly; (2) heating the mixture to 180° C. to melt the mixture, adding 0.5 kg of dibutyl iron dithiocarbamate (photosensitizer) and 2 kg of nano-mica (nano-inorganic filler), and continuing to disperse and mix; (3) Add the obtained coating material into the hopper of the coating machine, and at the same time load the base paper into the coating machine, spray the coating material onto the base paper, and obtain the photocatalytically degradable polyethylene coated paper after cooling and drying.
[0036] Example 4 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that the photo-oxidative degradation masterbatch used in this example is prepared in Preparation Example 2.
[0037] Example 5 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that the photo-oxidative degradation masterbatch used in this example is prepared in Preparation Example 3.
[0038] Example 6 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that the photo-oxidative degradation masterbatch used in this example is prepared in Preparation Example 4.
[0039] Example 7 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that the photo-oxidative degradation masterbatch used in this example is prepared in Preparation Example 5.
[0040] Example 8 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that the nano-montmorillonite used in this example is modified from Preparation Example 6.
[0041] Comparative Example Comparative Example 1 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that erucamide is not added in this example.
[0042] Comparative Example 2 A photocatalytically degradable polyethylene coated paper, which is different from Example 1 in that silicone powder is not added in this example.
[0043] Performance testing Detection method / test method Degradation performance: After irradiation with ultraviolet light for 720 hours at ambient temperature, the molecular weight before and after is analyzed by light scattering method, and the degradation rate of the coated paper is calculated; Tensile strength: According to GB / T1040.3-2006 "Film, Determination of tensile properties"; The elongation at break is tested in accordance with GB / T 1040-2018. The test conditions are 0°C, test speed 100mm / min, clamping length: 100mm, and tension 150N.
[0044] Table 1 Test results Degradation rate / % Tensile strength / MPa Elongation at break / % Example 1 90.23 45.67 180.45 Example 2 89.76 44.98 179.9 Example 3 90.34 45.23 180.12 Example 4 89.56 44.72 179.34 Example 5 90.01 45.39 180.28 Example 6 82.43 38.09 168.87 Example 7 85.65 41.32 171.67 Example 8 93.12 48.9 186.32 Comparative Example 1 84.34 39.76 174.43 Comparative Example 2 85.67 40.45 176.76 Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that the addition of erucic acid amide can reduce the friction and adhesion between polyethylene molecular chains and greatly improve the tensile strength and elongation at break of the coated paper.
[0045] Combining Examples 1-3 and Comparative Example 2 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2, indicating that the addition of silicone powder can form a uniform mixture with the polyethylene molecular chain, improve the processing performance of the laminated paper raw material, reduce defects in the preparation process, and improve the tensile strength and elongation at break of the laminated paper.
[0046] Combining Examples 1-6 and Table 1, it can be seen that the experimental data of Examples 1-5 are better than those of Example 6, indicating that on the one hand, the addition of Mxene material can improve the tensile strength of the laminated paper with its own good mechanical properties, and on the other hand, improve the degradation efficiency of the laminated paper, and its degradation rate is high under the same illumination time.
[0047] Combining Example 1 with Example 7 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 7, indicating that pre-sensitization of titanium dioxide by aromatic triazole is beneficial to improving the catalytic degradation effect of the photo-oxidative degradation masterbatch and further accelerating the degradation efficiency of polyethylene.
[0048] Combining Example 1 with Example 8 and Table 1, it can be seen that the experimental data of Example 8 are better than those of Example 1, indicating that further dispersing the nano inorganic filler is beneficial to improving its dispersion uniformity in polyethylene, thereby further improving the mechanical properties of the coated paper.
[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A photocatalytically degradable polyethylene coated paper, characterized in that: The composition comprises the following raw materials in parts by weight: 70-80 parts of polyethylene, 0.5-0.8 parts of erucic acid amide, 1-3 parts of photo-oxidation degradation masterbatch, 0.2-2 parts of silicone powder, 0.1-0.5 parts of photosensitizer, and 1-3 parts of nano inorganic filler. The photo-oxidation degradation masterbatch is obtained by loading titanium dioxide on Mxene material.
2. The photocatalytically degradable polyethylene coated paper according to claim 1, characterized in that: The photo-oxidative degradation masterbatch preparation comprises the following steps: (1) Dissolve tetrabutyl titanate in a mixed solution of ethanol and deionized water, add aryl triazole and sodium dodecyl sulfate, and dropwise add potassium permanganate solution at 150-200°C while stirring and react for 8-10 hours; (2) The temperature is lowered to 35-40°C, and the Mxene material is added and sealed and ultrasonicated until it is evenly dispersed. After reacting for 2-3 hours, the material is washed and dried to obtain a photo-oxidative degradation masterbatch.
3. The photocatalytically degradable polyethylene coated paper according to claim 2, characterized in that: The photo-oxidative degradation masterbatch comprises 4-6 parts of tetrabutyl titanate, 1-2 parts of sodium dodecyl sulfate, 16-20 parts of ethanol, 2-4 parts of water, 1-3 parts of potassium permanganate solution, 0.03-0.05 parts of aryl triazole, and 8-10 parts of Mxene material.
4. The photocatalytically degradable polyethylene coated paper according to claim 1, characterized in that: The nano inorganic filler is any one of nano montmorillonite, talc and mica.
5. The photocatalytically degradable polyethylene coated paper according to claim 4, characterized in that: The nano inorganic filler is obtained by surface activation modification, which specifically includes the following steps: After the nano inorganic filler is dispersed in water, a proper amount of titanate coupling agent is added and ultrasonic stirring is performed, and the mixture is reacted at room temperature for 1-2 hours. After the reaction is completed, the modified nano inorganic filler is obtained by drying.
6. The photocatalytically degradable polyethylene coated paper according to claim 1, characterized in that: The photosensitizer is dibutyl iron dithiocarbamate.
7. The photocatalytically degradable polyethylene coated paper according to claim 1, characterized in that: 0.3-0.5 parts of phthalocyanine ketone are also added to the raw materials.
8. A method for preparing the photocatalytically degradable polyethylene coated paper according to any one of claims 1 to 7, characterized in that: The steps include: (1) uniformly mixing polyethylene, photo-oxidative degradation masterbatch, silicone powder and erucamide to obtain a mixture; (2) heating and melting the mixture, adding photosensitizer and nano inorganic filler, and continuing to disperse and mix; (3) Spraying the obtained coating material onto the base paper, and obtaining the photocatalytically degradable polyethylene coating paper after drying.
Citation Information
Patent Citations
High-filling controllable oxidative degradation packaging material and preparation method thereof
CN102391557A
Flame-retardant scratch-resistant composite environment-friendly cable material and preparation method thereof
CN105131387A
Easily degraded PE (polyethylene) composition and preparation method thereof
CN108976549A
High-density polyethylene composition for waterproof coil material separation membranes, and preparation method thereof
CN108976571A
Degradable polyethylene agricultural film and preparation method thereof
CN109206727A